2015
DOI: 10.4103/0259-1162.150169
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical study comparing spinal anesthesia with isobaric levobupivacaine with fentanyl and hyperbaric bupivacaine with fentanyl in elective cesarean sections

Abstract: Background:To date, racemic bupivacaine is the most popular local anesthetic for spinal anesthesia in parturients undergoing elective cesarean delivery. With the introduction of levobupivacaine as pure S (–) enantiomer of bupivacaine which offers advantages of lower cardiotoxicity and neurotoxicity and shorter motor block duration, its use has widely increased in India. However, very few studies have been conducted about its efficacy in obstetric anesthesia. Thus, this study was undertaken to compare the senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These drugs have rapid onset, moderate duration of action, and low affinity to expand to the fourth vertebrae, and thus they are associated with a decreased risk of respiratory depression ( 21 ). Regardless of the wide use of opioids (6.25 - 50 mcg of fentanyl and 2.5 - 7.5 mcg of sufentanil) in combination with hyperbaric bupivacaine for Cesarean section, there is no consensus on the optimum dosage of fentanyl and sufentanil ( 3 , 5 - 7 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs have rapid onset, moderate duration of action, and low affinity to expand to the fourth vertebrae, and thus they are associated with a decreased risk of respiratory depression ( 21 ). Regardless of the wide use of opioids (6.25 - 50 mcg of fentanyl and 2.5 - 7.5 mcg of sufentanil) in combination with hyperbaric bupivacaine for Cesarean section, there is no consensus on the optimum dosage of fentanyl and sufentanil ( 3 , 5 - 7 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The local anaesthetic dose used was similar to that used by other authors in likewise studies. 14,15 Selection of ideal vasopressor for management of post-spinal hypotension is a matter of debate. Systematic reviews and meta-analysis of clinical trials demonstrated that phenylephrine and ephedrine were both effective in preventing postspinal hypotension.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows that 9 mg of bupivacaine resulted in a non-significant difference (p=0.987) in shivering between groups; however, the other doses resulted in a significant difference, with 10, 11, 12, and 13 mg doses exhibiting considerably higher shivering. The combination of 15 g of fentanyl and 1.8 mL of 0.5% bupivacaine (9 mg) was found to be an excellent dose combination for spinal anesthesia during cesarean section [14].…”
Section: Discussionmentioning
confidence: 96%